2016
DOI: 10.1371/journal.pone.0150118
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Transplantation in Disease Affecting Only One Eye: Does It Make a Difference to Habitual Binocular Viewing?

Abstract: BackgroundClarity of the transplanted tissue and restoration of visual acuity are the two primary metrics for evaluating the success of corneal transplantation. Participation of the transplanted eye in habitual binocular viewing is seldom evaluated post-operatively. In unilateral corneal disease, the transplanted eye may remain functionally inactive during binocular viewing due to its suboptimal visual acuity and poor image quality, vis-à-vis the healthy fellow eye.Methods and FindingsThis study prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The results of this study are in agreement with the previous literature on how increases in HOA's influence IQ in otherwise normal eyes 17,18,20,21 or in subjects who undergo LASER refractive surgery 16 or corneal transplants 29 . The latter two patient-based cohorts more closely resemble the present keratoconus cohort in that the increased HOA's and the associated reduction of IQ amplitude is rather long-standing and relatively more permanent than in normal eyes with induced HOA's.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are in agreement with the previous literature on how increases in HOA's influence IQ in otherwise normal eyes 17,18,20,21 or in subjects who undergo LASER refractive surgery 16 or corneal transplants 29 . The latter two patient-based cohorts more closely resemble the present keratoconus cohort in that the increased HOA's and the associated reduction of IQ amplitude is rather long-standing and relatively more permanent than in normal eyes with induced HOA's.…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore possible that these three patient cohorts may experience some form of neural recalibration to the altered retinal IQ that may enhance or negatively impact their visual performance 12,13 . Furthermore, unlike the refractive surgery and corneal transplant cohorts where the IQ deterioration may be relatively stable post-operatively 29,30 , the keratoconus cohort may experience a progressive deterioration of IQ with worsening of the disease. It would therefore be of interest for a future study to longitudinally track changes in IQ of eyes with progressing keratoconus and to compare them to changes in psychophysical visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…Stereoacuity (i.e., the smallest disparity that stimulates stereo depth) and the upper disparity limit (i.e., the largest disparity that stimulates stereo depth) are correlated with the overall magnitude and interocular differences in HOAs. More specifically, stereoacuity is worse in subjects with keratoconus and with surgical interventions like penetrating keratoplasty for corneal transplantation and LASIK refractive surgery, where HOAs are increased and mismatched between eyes (Bandela, Satgunam, Garg, & Bharadwaj, 2016; Nilagiri, Metlapally, Kalaiselvan, Schor, & Bharadwaj, 2018). On the other hand, the upper disparity limit that goes beyond the limit of binocular fusion (Duwaer, 1983; Howard & Rogers, 2012) is lowered with increasing interocular differences of HOAs (Jimenez, Castro, Hita, & Anera, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the upper disparity limit that goes beyond the limit of binocular fusion (Duwaer, 1983; Howard & Rogers, 2012) is lowered with increasing interocular differences of HOAs (Jimenez, Castro, Hita, & Anera, 2008). Also, stereoacuity losses are partially recovered when subjects switch from sphero-cylindrical spectacles to rigid gas-permeable contact lenses (RGP CLs) that minimize HOAs (Bandela et al, 2016; Nilagiri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…reported that RGP contact lenses improve the suppression threshold and stereoacuity in patients who have undergone PK in one eye. [ 21 ] RGP contact lens use after PK is considered to be safe if an acceptable fitting is achieved. In addition, RGP contact lenses do not affect endothelial cell density in eyes with corneal transplants even if the lenses are worn on a daily basis.…”
Section: Discussionmentioning
confidence: 99%